2009
DOI: 10.1039/b818104g
|View full text |Cite
|
Sign up to set email alerts
|

A photo-modulatable material for probing cellular responses to substrate rigidity

Abstract: Recent studies indicate that extracellular mechanical properties, including rigidity, profoundly affect cellular morphology, growth, migration, and differentiation [R. J. Pelham, Jr. and Y. Wang, Proc. Natl. Acad. Sci. U. S. A., 1997, 94(25), 13661–13665; H. B. Wang, M. Dembo and Y. L. Wang, Am. J. Physiol. Cell Physiol., 2000, 279(5), C1345–C1350; P. C. Georges, and P. A. Janmey, J. Appl. Physiol., 2005, 98(4), 1547–1553; C. M. Lo, H. B. Wang, M. Dembo and Y. L. Wang, Biophys. J., 2000. 79(1), 144–152; D. E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 28 publications
0
89
0
1
Order By: Relevance
“…1 Less attention is given to the role of the cellular microenvironment in this process, but it may be equally important for regulating cell function; for MSCs, chondrogenesis is conducted in pellet culture while osteogenesis is conducted in high cell density plate culture. 1 Further, the elasticity of the culture substrate has been shown to influence cell proliferation, adhesion, morphology, and migration and to direct MSC differentiation, 26 while patterning of substrates to control cell geometry has been shown to regulate relative cell growth and apoptotic rates. 7, 8 These results illustrate that a myriad of epigenetic factors, beyond soluble media additives, contribute to the control of cell function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Less attention is given to the role of the cellular microenvironment in this process, but it may be equally important for regulating cell function; for MSCs, chondrogenesis is conducted in pellet culture while osteogenesis is conducted in high cell density plate culture. 1 Further, the elasticity of the culture substrate has been shown to influence cell proliferation, adhesion, morphology, and migration and to direct MSC differentiation, 26 while patterning of substrates to control cell geometry has been shown to regulate relative cell growth and apoptotic rates. 7, 8 These results illustrate that a myriad of epigenetic factors, beyond soluble media additives, contribute to the control of cell function.…”
Section: Introductionmentioning
confidence: 99%
“…2932 Out of this work, photodegradable hydrogels have been developed that are fully compatible with cell culture. 6, 30, 33, 34 Studies with these materials have demonstrated control of the biochemical nature of the ECM to direct MSC differentiation, 30 channel formation to direct cancer cell migration, 30 and control of ECM elasticity to mediate the myofibroblast-to-fibroblast transition 34 or to direct cell morphology in 2D 6 and 3D. 33 …”
Section: Introductionmentioning
confidence: 99%
“…Fibroblasts, and in particular this standardized cell line, have been already investigated on stimuli responsive substrates [26,55,56] and were therefore chosen for the viability tests. Following ISO 10993-5 guidelines, magnetic hydrogels and controls were incubated at 37°C overnight in complete cell culture medium (Dulbecco's Modified Eagle's Medium supplemented with 10% v/v calf bovine serum, 2 mM L-glutamine 200 mM, and 1% v/v Penicillin-Streptomycin, cDMEM) and extracts of the solution were tested on fibroblasts for adverse effects.…”
Section: Biocompatibility Of Magnetic Hydrogelsmentioning
confidence: 99%
“…Used with permission. 23 biochemical supply and demand for raw materials necessary to adapt (which is highly influenced by transcription of genes that code for these raw materials including cytoskeletal, ECM and adhesion proteins). 10 The capacity to act, i.e.…”
Section: Mechanochemistry Of Stem Cell Adaptationmentioning
confidence: 99%
“…While many studies have documented diverse cell behaviors in response to combinations of biochemical and biophysical cues, outcome measures depend strongly on experimental conditions and/or the labs applying them. For example, over the past decade, observations of the intertwined roles of cell shape and lineage commitment as well as the associated role of the substrate compliance on cell shape and lineage commitment have spawned scores of further studies on the same topic, with some indicating a correlation between substrate compliance and lineage commitment [22][23][24] and others indicating quite the opposite. 25,26 In short, while the definition of libraries including different combinations of mechanical and/or chemical cues that could be used prescriptively to guide targeted lineage commitment, and with spatial and temporal fidelity, could be widely applicatied to regenerative medicine, such libraries have yet to be created.…”
Section: Introduction Backgroundmentioning
confidence: 99%